2009
DOI: 10.2337/dc08-1128
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pre-Diabetes and Its Association With Clustering of Cardiometabolic Risk Factors and Hyperinsulinemia Among U.S. Adolescents

Abstract: OBJECTIVE—Impaired fasting glucose (IFG) and/or impaired glucose tolerance (IGT) are considered to constitute “pre-diabetes.” We estimated the prevalence of IFG, IGT, and pre-diabetes among U.S. adolescents using data from a nationally representative sample. RESEARCH DESIGN AND METHODS—We analyzed data from participants aged 12–19 years in the National Health and Nutrition Examination Survey 2005–2006. We used fasting plasma glucose and 2-h glucose during an oral glucose tolerance test to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
219
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(269 citation statements)
references
References 24 publications
33
219
2
6
Order By: Relevance
“…The present study found no significant differences in FBG among ethnic groups (4.9 mmol/L on average) or the occurrence of impaired FBG, which was lower than the 13% reported among adolescents in NHANES (25). However, recent data from our SHARE study has shown that FBG levels can be higher among South Asian adults compared with European and Chinese Canadian adults (5.5 mmol/L, 5.2 mmol/L and 5.2 mmol/L, respectively) (9,10).…”
Section: Discussioncontrasting
confidence: 94%
“…The present study found no significant differences in FBG among ethnic groups (4.9 mmol/L on average) or the occurrence of impaired FBG, which was lower than the 13% reported among adolescents in NHANES (25). However, recent data from our SHARE study has shown that FBG levels can be higher among South Asian adults compared with European and Chinese Canadian adults (5.5 mmol/L, 5.2 mmol/L and 5.2 mmol/L, respectively) (9,10).…”
Section: Discussioncontrasting
confidence: 94%
“…[99][100][101] A hyperinsulinemic state is frequently observed in the development of type 2 diabetes as pancreatic production of insulin surges in an attempt to counteract the ever-increasing resistance of peripheral tissues. 102,103 Hyperinsulinemia may be capable of inducing the adipogenesis of cells within the marrow stem cell niche through a signaling cascade involving PKB and mTOR, culminating with activation of C/EBPa and PPARg. 104 Conversely, hypoinsulinemia, a hallmark of type 1 diabetes and an eventual occurrence following b-cell failure in type 2 diabetics, may also indirectly lead to enhanced adipogenesis.…”
Section: Hyper-and Hypo-insulinemiamentioning
confidence: 99%
“…Evidenced in the national study of 8th grade schoolchildren aged 13-15 years found that 40.2% of them were either overweight or obese (Ministry of Education, 2010). Obesity in the adolescence increases the risk of developing diabetes (Li C, Ford et al, 2009), leading to other health complications, including hypercholesterolemia and hypertension (Brophy, Cooksey et al 2009) and metabolic syndrome, where visceral obesity and insulin resistance are considered as main characteristics that determine a negative cardiovascular profile (Faloia, Michetti et al 2012).…”
Section: Introductionmentioning
confidence: 99%